PENINGKATAN PENGELOLAAN ASRAMA UNTUK MENUNJANG KUALITAS PELAKSANAAN PENDIDIKAN DAN PELATIHAN - Ummi Faizah (Universitas Negeri Malang, 2017)
The purpose of this research is to see the effectiveness of TQM implementation through ISO 9001: 2008 tools in preparation aspect of dorm room as supporting element in implementation of training implemented in PPPPTK BOE Malang. This study used descriptive qualitative method. The data is taken from the evaluation results of the implementation of the training in 2016. The results showed that the need for additional human resources both in quantity and quality, the addition of dormitory facilities, fund support and motivation from superiors in internalizing the implementation procedures that have been contained in ISO 9001: 2008.DOI: https://doi.org/10.17977/um025v1i32017p249